Impact of reduced inertia on transient stability of networks with asynchronous generation. (21st April 2015) - Naik, Prem Kumar; Nair, Nirmal‐Kumar C.; Swain, Akshya Kumar
Summary: This paper presents an energy function approach to assess power system transient stability impacts following increased penetration of asynchronous generation plants. Here, the asynchronous windfarm generation is considered as an equivalent conventional synchronous generator with negligible inertia. Assessment had been carried out on three‐machine nine‐bus test system to compute critical energy and critical fault‐clearing time using potential energy boundary surface method. A new representation of plotting contours of critical clearing times on inertia space is presented. This enables estimation of additional inertia required for a network in the event of inertia reduction of other machines. Results of the simulation and new graphical method confirm that transient stability margin of the system reduces with increased penetration of asynchronous generation. Copyright © 2015 John Wiley & Sons, Ltd.